Evaluation of efficacy and safety of single and multiple therapy of herbal medicine/Chuna therapy on non-specific chronic low back pain: A study protocol for multicenter, 3-arm, randomized, single blinded, parallel group, incomplete factorial design, pilot study. Issue 30 (24th July 2020) - Ko, Youme; Jang, Bo-Hyoung; Oh, Min-Seok; Kim, Sun Joong; Ko, Yeon-seok; Ha, In-Hyuk; Lee, Eun Jung; Kim, Me-riong; Song, Yun-Kyung; Ko, Seong-Gyu
Abstract: Introduction: Chronic non-specific low back pain is one of the common health issues which reduce the quality of life and in working population. While combined therapeutic treatment method is widely used for musculoskeletal related disorders in Korea, well-developed trials on the efficacy of single or combine therapy on herbal medicine and Chuna manual therapy (CMT) are scarce. Objective: This study aims to evaluate the clinical efficacy and safety of herbal medicine, Sogyeonghwalhyeol-tang (SGHH) on work related chronic low back pain patients. The primary aim is to determine the efficacy of a combined multidisciplinary approach using SGHH with CMT compared to SGHH alone. The secondary aim is to examine the naïve direct comparison between SGHH and placebo. Method: This trial is designed as a multicenter, randomized, controlled, clinical trial. A total of 150 participants who have with chief complaint of low back pain in Korean medicine rehabilitation center will be randomly assigned to 1 of 3 treatments with a ratio of 1:1:1. Eligible participant will be randomized to treatment arm A receive single treatment of Sogyeonghwalhyeol-tang, in treatment Arm B Sogyeonghwalhyeol-tang and Chuna manual therapy are administered concurrently, in treatment arm C, where individuals receive placebo with Chuna manual therapy. They will receive assigned treatment in 4 weeks and follow-up for 4 weeks. The primary endpoint is to assess the change in severity of low back pain from baseline. The secondary endpoints are the following: the changes in disability and health related quality of life. Adverse events will also be reported. Discussion: The study result will provide the valuable information for efficacy and safety of monotherapy and multiple therapy of herbal medicinal extract and Chuna manual therapy on chronic non-specific low back pain. Trial registration: ClinicalTrials.gov Identifier: NCT03132974. Abstract : Supplemental Digital Content is available in the text